A starch/gelatin-based Halochromic film with black currant anthocyanin and Nanocellulose-stabilized cinnamon essential oil Pickering emulsion: towards real-time Salmon freshness assessment - Lim, Hong Jun; Tang, Siah Ying; Chan, Kim Wei; Manickam, Sivakumar; Yu, Lih Jiun; Tan, Khang Wei (Elsevier, 2024)
Neoterically, food packaging systems designed solely for prolonging shelf life or monitoring freshness could not fulfil the dynamic demands of consumers. In this current investigation, using the solvent casting method, a versatile halochromic indicator was created by integrating black currant anthocyanin and cinnamon essential oil-loaded Pickering emulsion into a starch/gelatin matrix. The resulting indicator film underwent scrutiny for its structural, pH-sensitive, antioxidant, and antimicrobial attributes. Unexpectedly, the amalgamation of anthocyanin and essential oil led to decreased antioxidant activity, dropping from 73.23 ± 2.17 to 28.87 ± 2.50 mg Trolox equivalent/g sample. Additionally, no discernible antimicrobial properties were detected in the composite film sample against both Staphylococcus aureus and Escherichia coli. Fourier transform infrared analyses unveiled robust intermolecular interactions among the film-forming components, providing insights into the observed antagonistic effect. The indicator film displayed distinctive colour changes corresponding to the fresh (greyish-brown), onset of decomposition (khaki), and spoiled (dark green) stages of the stored fish sample. This highlights its promising potential for providing real-time indications of food spoilage. These findings are important for the efficient design of composite films incorporating anthocyanins and essential oils. They serve as a guide towards their potential use as multifunctional packaging materials in the food industry.